A computer simulation study of the hierarchical assembly behaviour of triblock patchy particles. Issue 9 (13th June 2019) - Li, Yan-Chun; Zhang, Ni-Boqia; Wei, Zhen; Li, Bing-Yu; Li, Mei-Ting; Li, Yang
ABSTRACT: We study the hierarchical self-assembly behaviour of ACB triblock patchy particles via Brownian dynamics (BD) simulations, where the product of the first stage is set as the initial structure for the second stage. We offer a promising design rule to investigate the assembly mechanism of ACB triblock patchy particles in selective solvent conditions by two-stage optimisation. At the first stage, the attractive hydrophobic interactions only exist between patches A at low concentration in order to generate subunits. At the second stage, the attractions also exist between patches B for studying the assembly process from subunits to target structures by heating/cooling method. By regulating the interactions between patches B as well as the concentrations of patchy particles, the ordered structures that determined by various influence factors are studied. Via properly designing the assembly models and routes, we can observe the formation process of simple cubic lattice and kagome lattice structures, respectively. The results reveal that the concentration and attractive strength play the critical roles in the whole process of hierarchical self-assembly.